Does Lateral Release Change Patellofemoral Forces and Pressures?: A Pilot Study - Peretz, Jeffrey I. (Springer-Verlag, 2011)
BACKGROUND: One complication of TKA is postoperative anterior knee pain. Balancing retinacular tissue tension to improve patellar tracking is essential in preventing pain. Lateral release might help balance tension although the quantitative changes in patellofemoral force and pressure differentials after lateral release are unknown. QUESTIONS/PURPOSES: We asked if there are differences in patellofemoral forces and pressures for knees resurfaced with standard and gender-specific components and whether lateral release changes these differentials. METHODS: We studied six fresh-frozen cadaver knees with native knees and knees that had TKAs with patellofemoral resurfacing using traditional and gender-specific components. The knees were taken through passive ROM, and the means for medial and lateral peak pressure and maximum force were calculated before and after a lateral release was performed. RESULTS: In traditional resurfaced knees, lateral peak pressure was greater than medial peak pressure by 727.6 ± 550.0 kPa and lateral maximum force was greater than medial maximum force by 29.6 ± 15.9 N. Lateral release decreased the pressure (71.4 ± 826.0 kPa) and force (10.0 ± 32.1 N) differentials in the traditional but not in the gender-specific design. In gender-specific resurfaced knees, lateral peak pressure was greater than medial peak pressure by 158.7 ± 360.0 kPa and lateral maximum force was greater than medial maximum force by 15.5 ± 10.4 N. Lateral release increased the pressure (285.7 ± 565.0 kPa) and force (16.8 ± 10.8 N) differentials. CONCLUSIONS: Our preliminary data suggest lateral release is more effective in reducing peak pressure and maximum force differentials in knees resurfaced with traditional standard components than with gender-specific components. CLINICAL RELEVANCE: The lateral release technique might help with tissue balancing when using standard components in TKA.